Classifications and perceptions associated with knowledge of the firewood used in a rural community of Chaco Seco (Catamarca, Argentina) - Jiménez-Escobar, N. David (Instituto de Ecología, A.C., 2021)
Background and Aims: Firewood is one of the main sources of energy for rural populations in various environments and ecosystems around the world. It is a priority to establish, from a local point of view, the main sets of knowledge and perceptions related to the use of these wood-energy resources, defining which are the main terms and categories related to firewood in the Sierra de Ancasti, Province of Catamarca, Argentina. Methods: By means of the “snowball” technique and through to open and semi-structured interviews in 46 domestic units, guided walks, collection of botanical specimens, herbarium work and literary revision, the main perceptions associated with the use and knowledge of firewood species were established. To obtain the local classification categories and vernacular terms associated with firewood, a “word game” was proposed. Using sets and Venn diagrams and a Principal Component Analysis (PCA), species groupings were identified according to local categories, terms and definitions.Key results: The rural inhabitants indicated, from 74 common names, 53 species of firewood, corresponding to 45 genera and 23 botanical families. A high percentage of species of native origin stands out (74%). In 456 mentions, for 40 species, a total of 25 terms related to the properties of wood and related to combustion and fire were registered. The terms most used by the rural inhabitants to describe and classify a firewood are: “strong” (52 mentions, associated with 11 species), “firm” (39, 13 spp.), “cute” (33, 13 spp.) and “easy to extinguish” (30, 11 spp.).Conclusions: At present, the inhabitants recognize, describe and identify the firewood. They use characters that are related to the ember, highlighting as positive attributes characteristics related to caloric power and duration. The need is emphasized to address the social dynamics related to the environment from the field itself, as a way of knowing local priorities and channeling efforts for biological and cultural conservation.